EFFORTS TO OVERCOME THE CRIME OF MONEY LAUNDERING (PADANG LAWAS POLICE RESEARCH STUDY) - Ilmuwani Lubis; Karolus Agung Dery Rianto; Irfan Rizky Pradya; Willy Novan Prakoso; Stephen Martin (Journal of International Islamic Law, Human Right and Public Policy, 2023)
Money laundering, often known as money laundering, is carried out by government officials who hold the power to recover illegal money after getting results that do not belong to them. In Indonesian, money laundering is translated as "money laundering" or "money bleaching". Article 3 of Law Number 8 of 2010 concerning Prevention and Eradication of the Crime of Money Laundering states that every person who places, transfers, diverts, spends, pays, grants, entrusts, takes abroad, changes the form, exchanges for currency or securities or acts other assets which he knows or reasonably suspects are the proceeds of a crime with a maximum imprisonment of 20 (twenty) years and a maximum fine of Rp. 10,000,000,000.00 (ten billion rupiah). Based on research at the Special Investigation Unit of the Padang Lawas Police, there was a crime of money laundering. However, in reality there are still obstacles in solving the crime of money laundering. This research aims to explain the law enforcement process by the Criminal Investigation Unit of the Medan Police Special Investigations Section in the crime of money laundering, the efforts made by the Padang Lawas Police Criminal Investigation Unit in dealing with criminal acts of money laundering and the obstacles faced by the Special Criminal Investigation Unit of the Padang Lawas Police Special Investigations Section in tackling the crime of money laundering.